Health Care Utilization and Anti-Cancer Drug Expenditure for Six Solid Cancers in Korea From 2007 to 2019 - Park, Juhee; Moon, Kyeongjun; Kim, Dong-Sook (Frontiers in Oncology, 2022)
Background: The burden of care continues to rise considerably worldwide and the challenge of diversity in cancer research has become important. We aimed to examine trends of cancer care utilization and anti-cancer medication among patients with six solid cancers (gastric, colorectal, liver, lung, breast, and prostate cancer) in South Korea. Methods: This study analyzed patients diagnosed with six types of solid cancer from 2007 to 2019 using data from the National Health Insurance claims database. We analyzed the total number of cancer cases, each patient’s length of stay (LOS) in a hospital, the number of outpatient physician visits, total medical care costs, total out-of-pocket (OOP) costs, and expenditures on anti-cancer drugs. Results: Utilization of healthcare services and spending on cancer care including anti-cancer drugs both increased in the 13-year study period. The average LOS was the highest for colorectal cancer patients at 43.5 days, and breast cancer patients had the highest average number of physician visits at 11.8. Breast cancer patients had the highest total medical costs (USD 923 million), anti-cancer drug spending (USD 156 million), and the largest increase (5 times) over the 13-year period. The anti-cancer drugs with the largest market shares were ramucirumab for gastric cancer; oxaliplatin for colorectal cancer; sorafenib for liver cancer; pembrolizumab, nivolumab, for lung cancer; trastuzumab for breast cancer; and bicalutamide for prostate cancer. Conclusion: This study was a large-scale analysis from a nationally representative database of the total population. The study also shows the pattern of cancer care in an Asian country and can provide implications for future cancer research.